Studi Perbandingan bentuk Pertanggung Jawaban Pidana terhadap Pelaku Tindak Pidana Pembunuhan yang Mengalami Gangguan Jiwa Menurut Hukum Islam dan Hukum Positif Indonesia - Asad Shadiq; Sukmareni Sukmareni; Riki Zulfiko (UNES Law Review, 2023)
Murder committed by persons with mental disorders is a common problem in society with various cases and characteristics. The news about this is likely to evoke strong emotions and raise questions about whether to be sanctioned or not. With regard to the crime itself, the view of Islamic law defines a criminal act as an act prohibited by law that comes from Allah, for this violation there is already a provision for punishment that comes from Him. The legal prohibition referred to here is doing something that has been prohibited or by not doing work that is not justified. What can be classified as part of a criminal act in Islam is if the act is only prohibited on the basis of the Shari'a. This must be said, by doing or not doing an act that will result in a punishment that must be based on the Shari'ah which is a crime. Comparison of Islamic law and in the provisions of criminal law against acts in the category of criminal acts, such as acts in the category of murder, which are committed by those who are experiencing mental disorders. Here it will be seen whether the form of Islamic law and the form of criminal law will also be applied to people with mental disorders who have been proven to have committed the crime. The research method used is a normative juridical approach, namely law that focuses on the study of library data as secondary data, in the form of positive law and governing Islamic law. Based on the results of research in positive law criminal offenders who experience mental disorders cannot be punished as well as in Islamic law, however there are slight differences that require criminal offenders who experience mental disorders to pay compensation which is borne by the offender's family.